Elements of Precision Agriculture in Malting Barley Cultivation and the Use of Barley Straw for Energy Purposes (Agricultural Engineering, 2020)
The paper presents the results of research on the mass and the energy potential of malting barley straw of the “Klas” variety. The research was designated on a 100 ha plantation located in Pojezierze Iławsko-Sztumskie region. Using the Yara N-Sensor processor, precise application of mineral fertilizers according to determined fertilization demand allowed increasing the grain yield by 26% and the straw biomass yield by 74% compared to the control sample. The resulting increase in bio-mass obtained in the form of straw impacts its possible partial use for energy purposes without negative effects on the environment. The tested energy value of malting barley straw as a function of moisture content allowed a conclusion that between 10 and 25% of water content the energy value drops from 13.1 to 7.4 GJ∙t−1. For an average water content of 15%, this yields an energy potential unit of 23.76 GJ∙ha−1. Following observations of the combustion process, it was concluded that barley straw cannot be used as a source of biomass for the large-scale power production since its ash melts at below 800ºC.